Gaya Kepemimpinan Kepala Madrasah dalam Mengatasi Masalah Kinerja Guru di MA NW Tampih: The Principal's Leadership Style in Addressing Teacher Performance Problems at MA NW Tampih - Nasrullah (Pendidikan Al-Gafari, 2026)
This study aims to analyze the influence of the principal's leadership style on improving teacher performance at MA NW Tampih. The approach used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the principal applies a participatory and transformational leadership style that involves teachers in the decision-making process, program evaluation, and development of learning strategies. This leadership style has a positive effect on teacher performance, characterized by increased motivation, discipline, active participation, and innovation in the learning process. Teachers feel valued, trusted, and supported to develop professionally, which ultimately has an impact on improving the quality of education. These findings indicate that collaborative and communicative leadership is key to creating a productive work environment oriented towards improving performance.